To the Question of the Perfoming Fate of Piano Sonatas in Uzbekistan - Sidikova Aliya Maratovna (International Journal on Integrated Education, 2021)
Questions of musical and performing interpretation of the Sonata genre did not receive sufficient and thorough studies in modern music. This is especially true of the prosuses of the last decades created by Uzbek composers. There is a real need to analyze and understand what place the piano sonata is occupied in the composer work and in the executive practice of modern Uzbekistan, which the stable parameters of the genre appeared, and where the desire of domestic authors would connect to the national musical traditions and the experimental trends in Western Music of Postmodern Epoch. But the main thing is that the problem of the executive destiny of Uzbek piano sonata remains relevant, its further prospects to be, to sound on the concert scene, to gain their listeners and connoisseurs.